Science, red in tooth and claw: Whaling, purity, pollution and institutions in marine mammal scientists' boundary work. (March 2018) - Singleton, Benedict E.; Lidskog, Rolf
The use of lethal research methods on cetaceans has a long and complicated history in cetology (the scientific study of whales, dolphins and porpoises). In the current era, collecting data through the hunting of whales (sometimes referred to as scientific whaling) remains a source of considerable conflict in various fora, including scientific ones. Based on interviews and documents, this article explores how marine mammal scientists articulate the validity of particular practices and research at both the International Whaling Commission and in professional scientific societies. Drawing on cultural theory, the article explores scientists' boundary work, describing the purity and pollution of particular whaling practices in different institutional contexts. Respondents on either side of the debate argued for the pure or polluted nature of various positions, often utilising particular idealised values of science: objectivity, honesty and openness regarding how conclusions were drawn. The nature of boundary work performed is then related to the institutional context within which it takes place. This article thus highlights how science's role in environmental conflicts can be assessed through boundary work that denotes who can legitimately speak for science, on what topics and how science is stage-managed.